Life in the Pits: Competitive Market Making and Inventory Control - Manaster, Steven; Mann, Steven C. (Review of Financial Studies, 1996)
[We use futures transaction data to investigate cross-sectional relationships between market-maker inventory positions and trade activity. The investigation documents strongly that traders control inventory throughout the trading day. Despite this evidence of inventory management, typical inventory control models are contradicted by our data. These inventory models predict that market-maker reservation prices are negatively influenced by inventory. Surprisingly, our evidence shows, as a strong and consistent empirical regularity, that correlations between inventory and reservation prices are positive. We interpret the evidence as consistent with active position taking by futures market floor traders.]